Team‐based learning in nursing education: A scoping review. Issue 7 (4th January 2021) - Considine, Julie; Berry, Debra; Allen, Joshua; Hewitt, Nicky; Oldland, Elizabeth; Sprogis, Stephanie K.; Currey, Judy
Abstract: Aims and objectives: To explore the use and student outcomes of Team‐Based Learning in nursing education. Background: Team‐Based Learning is a highly structured, evidence‐based, student‐centred learning strategy that enhances student engagement and facilitates deep learning in a variety of disciplines including nursing. However, the breadth of Team‐Based Learning application in nursing education and relevant outcomes are not currently well understood. Design: A scoping review of international, peer‐reviewed research studies was undertaken according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for scoping reviews. Methods: The following databases were searched on 7 May 2020: Cumulative Index of Nursing and Allied Health Literature, MEDLINE Complete, PsycINFO and Education Resources Information Center. Search terms related to nursing, education and Team‐Based Learning. Original research studies, published in English, and reporting on student outcomes from Team‐Based Learning in nursing education programmes were included. Results: Of the 1081 potentially relevant citations, 41 studies from undergraduate ( n = 29), postgraduate ( n = 4) and hospital ( n = 8) settings were included. The most commonly reported student outcomes were knowledge or academic performance ( n = 21); student experience, satisfaction or perceptions of Team‐Based Learning ( n = 20); student engagement with behaviours or attitudes towards Team‐Based Learning ( n = 12); and effect of Team‐Based Learning on teamwork, team performance or collective efficacy ( n = 6). Only three studies reported clinical outcomes. Conclusions: Over the last decade, there has been a growing body of knowledge related to the use of Team‐Based Learning in nursing education. The major gaps identified in this scoping review were the lack of randomised controlled trials and the dearth of studies of Team‐Based Learning in postgraduate and hospital contexts. Relevance to clinical practice: This scoping review provides a comprehensive understanding of the use and student outcomes of Team‐Based Learning in nursing education and highlights the breadth of application of Team‐Based Learning and variability in the outcomes reported.